Metabolic Dysfunction Associated Steatotic Liver Disease (MASLD), An Underappreciated Threat. - Omer Buzaid, Najat; A. Lawgaly, Sami (Benghazi University Medical Journal, 2025)
Dear editor A 56-year-old woman was presented to the outpatient clinic with a dull aching pain in the right upper abdominal quadrant. She was diagnosed with type 2 diabetes mellitus (T2DM) three years ago, and she is taking Metformin tablets as the sole medication. Her body mass index (BMI) was 32 kg/m2. An abdominal ultrasound scan revealed a single gall bladder stone and fatty liver. The platelets count was 150x103/ml; aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were 50 U/L and 40 U/L, respectively. Serological testing for viral hepatitis was negative. Other metabolic and autoimmune causes of liver disease were excluded. What would be the most appropriate next step in management? A.Reassurance and no further treatment is needed. B.Liver elastography is indicated. C.Liver biopsy is indicated urgently. Metabolic dysfunction associated steatotic liver disease (MASLD)- previously known as non-alcoholic fatty liver disease (NAFLD)- is a common health problem with an increasing prevalence globally. Its more sever